2004
DOI: 10.1111/j.1365-2664.2004.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive control of invasive vegetation: a native wetland sedge suppresses Phalaris arundinacea in carbon‐enriched soil

Abstract: Summary 1.Invasive plants pose a major threat to native plant communities around the globe. Current methods of controlling invasive vegetation focus on eradication of existing populations, and are often effective only in the short term. Manipulating resource availability to give native species a competitive advantage over invasive species could reduce ecosystem vulnerability to invasion and might more effectively control invasive vegetation. We evaluated this approach for controlling invasions of sedge meadow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 53 publications
9
118
0
Order By: Relevance
“…Also, labile C sometimes increases N availability, such as when plant rhizodeposition increases N mineralization (i.e., priming; Jones et al 2004) or when low inorganic N stimulates biological N 2 Wxation. However, most C addition studies that have measured N have observed signiWcantly lower inorganic N with C addition (e.g., McLendon and Redente 1992;Schmidt et al 1997;Young et al 1997;Zink and Allen 1998;Michelsen et al 1999;Morghan and Seastedt 1999;Paschke et al 2000;Cione et al 2002;Baer et al 2003;Blumenthal et al 2003;Monaco et al 2003;Averett et al 2004;Perry et al 2004;Suding et al 2004b;Huddleston and Young 2005;Prober et al 2005;Vinton and Goergen 2006;Bleier and Jackson 2007;Eschen et al 2007;Iannone et al 2008;Blumenthal 2009;Rowe et al 2009). Further, factorial experiments with C and N addition treatments have indicated that negative eVects of C addition on plant growth are due to lower N availability (Schmidt et al 1997;Michelsen et al 1999;Blumenthal et al 2003;Perry et al 2004), although other mechanisms are possible, including immobilization of other nutrients, altered microbial community composition (Klein et al 1996), or release of phytotoxic compounds during decomposition or fermentation (Ishii and Kadoya 1993).…”
Section: Soil C Additionmentioning
confidence: 97%
“…Also, labile C sometimes increases N availability, such as when plant rhizodeposition increases N mineralization (i.e., priming; Jones et al 2004) or when low inorganic N stimulates biological N 2 Wxation. However, most C addition studies that have measured N have observed signiWcantly lower inorganic N with C addition (e.g., McLendon and Redente 1992;Schmidt et al 1997;Young et al 1997;Zink and Allen 1998;Michelsen et al 1999;Morghan and Seastedt 1999;Paschke et al 2000;Cione et al 2002;Baer et al 2003;Blumenthal et al 2003;Monaco et al 2003;Averett et al 2004;Perry et al 2004;Suding et al 2004b;Huddleston and Young 2005;Prober et al 2005;Vinton and Goergen 2006;Bleier and Jackson 2007;Eschen et al 2007;Iannone et al 2008;Blumenthal 2009;Rowe et al 2009). Further, factorial experiments with C and N addition treatments have indicated that negative eVects of C addition on plant growth are due to lower N availability (Schmidt et al 1997;Michelsen et al 1999;Blumenthal et al 2003;Perry et al 2004), although other mechanisms are possible, including immobilization of other nutrients, altered microbial community composition (Klein et al 1996), or release of phytotoxic compounds during decomposition or fermentation (Ishii and Kadoya 1993).…”
Section: Soil C Additionmentioning
confidence: 97%
“…The reduction in soil N may prevent fast growing exotic species and ultimately favour re-establishment of native species (Hulme 2006;Kulmatiski et al 2006;Maron and Jefferies 2001;Perry et al 2004). Controlled burns are sometimes used to reduce C and N pools (Haubensak et al 2004), but it may not be efficient in decreasing available N in the short term (Prober et al 2005).…”
Section: Contributions For Managementmentioning
confidence: 99%
“…Since the competitive balance can be shifted by environmental stresses, Perry et al (2004) have proposed that manipulating environmental conditions to give native species a competitive advantage over invasive species could reduce ecosystem vulnerability. The tidal flats and marshes in the Yangtze River estuary are strongly affected by the tidal water flow, so the artificial alterations to environmental factors might be less effective.…”
Section: Some Implicationsmentioning
confidence: 99%